Capacitación - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Training of scientists and extensionists at CIAT headquarters in the development, testing, and promotion of new breeding lines and agronomic practices continued to receive high priority in the bean program. A total of 180 scientists from El Salvador, Costa Rica, Nicaragua, Peru, Honduras, and Colombia were trained this year in on-farm research. Seventy-six scientists from the Americas, Europe, Asia, and Africa received training in various disciplines. Data are included on training provided at CIAT in specific disciplines and the no. of man-mo. of training provided by CIAT, by country; a list is included with name of trainee, country, institution, discipline, supervisor, and scientist-mo. at the bean program. (CIAT)